Spawning, larval development and spat settlement of the clam, Meretrix casta (Chemnitz) in the laboratory - Sreenivasan, P V; Rao, K Satyanarayana (Indian Journal of Fisheries, 2011)
The clam, Meretrix casta (Chrannitz) ofFamily Venwidae, is one of the commerciallyimpOTtant bivalves in India (Al^arswami andMeiyiqjpan 1989). Itiswidelydistributedatongthe east and southwest coasts of India andformssustenance fishoy in themmtime statesof KamataKa, Kerala, Tamil Nadu and AndhtaPradesh. Besides fishing of Uve cUms, extensivequarrying of sub-fossil cteposits of thisspecies is carried out alcMig the coasts.